2021
DOI: 10.1111/apps.12337
|View full text |Cite
|
Sign up to set email alerts
|

Followership at a distance: Follower adjustment to distal leadership during COVID‐19

Abstract: Leader distance theory has received scant empirical attention in the extant literature; however, the "work from home" orders associated with COVID-19 have made this theory and its empirical findings highly relevant for organizations. Our study integrates leader distance theory and followership theory to understand how follower role beliefs affect follower effort, performance, and withdrawal under physical leader distance and varying conditions of leader interaction frequency. Using a three-wave survey methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…with possible choices being "strengthened," "weakened," "not changed," or "made me think differently about my leadership identity." Of 1218 responses to this question, 754 participants contributed additional open-ended responses to explain their multiple-choice selection which we analyzed using thematic coding [3][4][5] and constant comparison method [6] until saturation. We also disaggregated the quantitative multiple-choice data by each demographic variable (gender, race, and location of engineering training) and plotted the proportions of each group who identified strengthened, weakened, different, or no change in the leadership.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…with possible choices being "strengthened," "weakened," "not changed," or "made me think differently about my leadership identity." Of 1218 responses to this question, 754 participants contributed additional open-ended responses to explain their multiple-choice selection which we analyzed using thematic coding [3][4][5] and constant comparison method [6] until saturation. We also disaggregated the quantitative multiple-choice data by each demographic variable (gender, race, and location of engineering training) and plotted the proportions of each group who identified strengthened, weakened, different, or no change in the leadership.…”
Section: Methodsmentioning
confidence: 99%
“…An editorial in the Australian Journal of Rural Health explored the relevance of leadership values, governance, communication, and (interestingly) analogies to physics, in the context of public health [7]. A relevant study by Carsten et al investigated experiences of followership during COVID-19 through the lens of leader distance theory, finding that respondents with a collaborative leadership orientation struggled to adapt to distance more than those with a more passive orientation [6]. In spring of 2020, only a few months into the pandemic, Dirani et al produced a list of leadership competencies for effective crisis response in their study of the role of human resource development [3].…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies, especially with the implicit followership theory (IFT), revealed the importance of positive relationships between leaders and followers that are formed over time and grounded in trust to work in partnership on organizational goals and to stay engaged (Gao & Wu, 2019; Kong et al., 2019; Yip & Walker, 2022; Veestraeten et al., 2021). Research with Followership Theory (FT) made a significant positive connection between followers’ effort and leader interaction frequency, again putting relationships and time involved in developing relationships as an important mediating factor of productive leader‐follower work (M. Carsten et al., 2022).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Other articles examined more comprehensively how leaders managed employees and how employees responded to their leaders during the pandemic crisis. Carsten et al (2022) explored how followers responded to distal leadership, a situation where the leader does not interact on a face‐to‐face basis with their followers, during the COVID‐19 pandemic. They found that followers with a coproduction role orientation, who see their role as being more collaborative, as opposed to a passive role orientation, reported higher levels of effort under conditions of high leader interaction.…”
Section: Current Contributions Of the Special Issuementioning
confidence: 99%